Developing millennial tree-ring chronology for Turku (Åbo) and comparing palaeoclimatic signals inferred from archaeological, subfossil and living Pinus sylvestris data in Southwest Finland - Helama, Samuli (Poland, 2025)
Archaeological and living tree data were used to construct tree-ring chronologies over the medieval (AD 1183–1430) and recent (AD 1812–2020) periods in Turku, which is historically an important population centre in Southwest Finland and the country. Comparisons between the two tree-ring assemblages, and between the previously built chronologies from the Åland (historical timber) and Tavastia (lacustrine subfossils and living trees) sites, provided ways of understanding the growth patterns and their linkages to climatic, environmental, and edaphic factors. Tree growth in and around Turku was affected by warm-season precipitation and winter temperature. Similar relationships were previously evident also in the Åland tree rings, whereas the data from a wetter Tavastia site did not exhibit similar precipitation signal. The site conditions influence also the correlations which are higher between Turku and Åland than  between Turku and Tavastia chronologies. Construction of long continuous chronology is impaired by human-related activities, the Great Fire of Turku in 1827 and logging, which have diminished the availability of dead and living-tree materials, respectively. These conditions lead to hardships of filling the gap between the medieval and recent periods and updating the archaeological datasets with compatible living-tree data, which are both demonstrated by our results.